Specific heat of CeIn3-xSnx single crystals in the vicinity of the quantum critical point - Rus, T. (2005)
Fil: Sereni, J.G. Comisión Nacional de Energía Atómica. Instituto Balseiro. Laboratorio de Bajas Temperaturas; Argentina